Marginalization in China - Lee, Joseph Tse-Hei. author. aut Link
XII, 263 p. 2 illus.
Keywords: Bringing together historians, sociologists, and political scientists, this volume documents persistent prejudices against consistently marginal groups in China, and the moral claims they have mustered in response.